2022
DOI: 10.3389/fneur.2022.925797
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Lesion Size and Sensorimotor Responses Following Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a devastating disorder, which impacts the lives of millions of people worldwide with no clinically standardized treatment. Both pro-recovery and anti-recovery factors contribute to the overall outcome after the initial SCI. Sex is emerging as an important variable, which can affect recovery post-SCI. Contusion SCI at T10 was generated in male and female rats. Open-field Basso, Beattie, Bresnahan (BBB) behavioral test, Von Frey test, and CatWalk gate analysis were performed. Histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…The previous work in our [1] and other [4,5] laboratories provided evidence that following SCI in rodents, sex differences existed in outcomes in which females exhibited improved locomotor recovery and greater preservation of both white and gray matter compared to males [1]. In two subsequent studies, female rodents showed reduced lesion sizes and faster sensory recovery after SCI [6] or displayed a lower neuroinflammatory response, improved locomotor function, better cognitive performance, and less depressive-like behaviors than age-matched male animals, a finding that was more pronounced when SCI occurred at a young adult age [7]. Within the human SCI patient population, the lower incidence of injury among females limits the acquisition of adequate clinical data for comparing the extent of functional recovery or prognosis of SCI between sexes.…”
Section: Introductionmentioning
confidence: 79%
“…The previous work in our [1] and other [4,5] laboratories provided evidence that following SCI in rodents, sex differences existed in outcomes in which females exhibited improved locomotor recovery and greater preservation of both white and gray matter compared to males [1]. In two subsequent studies, female rodents showed reduced lesion sizes and faster sensory recovery after SCI [6] or displayed a lower neuroinflammatory response, improved locomotor function, better cognitive performance, and less depressive-like behaviors than age-matched male animals, a finding that was more pronounced when SCI occurred at a young adult age [7]. Within the human SCI patient population, the lower incidence of injury among females limits the acquisition of adequate clinical data for comparing the extent of functional recovery or prognosis of SCI between sexes.…”
Section: Introductionmentioning
confidence: 79%
“…We observed that KA-lesioned animals have significantly higher CA step sequences, as opposed to the more commonly seen AB sequence. Previous papers have reported speed can influence step sequence in mice and rats and that a faster gait corresponds to AB sequence [ 64 , 65 ]. As our KA-lesioned rats have significantly slower body speed, this change in gait pattern is not surprising.…”
Section: Discussionmentioning
confidence: 99%